ADVANCES IN WATER QUALITY ASSESSMENT USING FUZZY APPROACH: RECENT TRENDS OF THEORY AND APPLICATIONS - Syafiza Saila Samsudin; Afida Ahmad; Norliana Mohd Najib (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
Due to the rapid growth of economic development and population, the demand for water consumption and the levels of polluted water in Malaysia have constantly increased and are considered crucial issues in Malaysia. Urbanization has steadily produced great amounts of human wastes, such as domestic and industrial wastes which inevitably end up in the water bodies. The World Health Organization claimed that approximately 2.2 million people die annually from such illnesses caused by ingesting bacteria, viruses, protozoans, and other pathogenic microbes in untreated or poorly treated waters or wastewater. This paper intends to provide insight into the publication trends on water quality assessment using fuzzy approaches from 2015 to 2023. This study conducted a bibliometric analysis of 404 scholarly works on water quality assessment as recorded in the Scopus database in September 2023. The data was analysed using a variety of software which are VOSviewer, Harzing’s Publish and Perish, and Microsoft Excel. This paper highlights important contributions, publications, statistics, and current trends of theory and applications in the field. The finding also addresses essential information on present and future developments and critical information for increasing the inclusivity and global reach of water quality assessment which need further attention from the fuzzy research community.